The effects of flexion-distraction and drop techniques on disorders and Ferguson’s angle in female patients with lumbar intervertebral disc herniation - Oh, Hyunju (J Phys Ther Sci, 2018)
[Purpose] This study examines the effects of the flexion-distraction technique and the drop technique on disorders and on Ferguson’s angle in female patients with lumbar intervertebral disc herniation. [Subjects and Methods] Thirty female patients with lumbar intervertebral disc herniation were divided into an experimental group (n=15) treated with flexion-distraction and drop techniques and a control group (n=15) treated with spinal decompression therapy. Both groups were treated three times a week over an eight-week period. [Results] In the comparison of changes within each group after treatment, both groups showed statistically significant decreases in disorders and in Ferguson’s angle. [Conclusion] Flexion-distraction and drop techniques may be an effective intervention to improve disorders and Ferguson’s angle in female patients with lumbar intervertebral disc herniation.